Landscaping is a priority for development - Saidova, Navruza; Madiev, Farrukh (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Creating good conditions for recreation and work of cultural and social services to the population, in solving these tasks, a comprehensivestudy of the urban environment, new scientific and technical achievements and engineering measures in the field of engineering beautification of urban and rural areas Ensure that the solution is studied and taken into account